A critical review on different casting technique to develop the composite material and its tribo-mechanical behaviour. (2021) - Kumar, Rohit; Pradeep, Sajal; Singh, Rishabh; Dubey, Ritesh; Dwivedi, Shashi Prakash
Abstract: Nowadays, there are various types of techniques have been used to develop the composite material by using various types of reinforcement particles. In the present review article, different techniques have been discussed for the development of aluminum-based composite material. Furthermore, the percent utilization of different reinforcement particles has been also discussed. Mechanical properties of the developed composite were also discussed. It was identified from the literature that normal load, sliding velocity, sliding distance, and reinforcement weight percent also affect significantly the tribological behavior of composite material.